A cadeia produtiva do café: uma análise da produção acadêmica brasileira e o impacto da denominação de origem do café na criação de vantagem competitiva da Região do Cerrado Mineiro - Souza, Ariany Pena de (2018)
The coffee production chain is the theme of this dissertation and its importance is related to the representativeness of this chain in the agribusiness activities of Minas Gerais and Brazil, and the relevance of the improvement of management techniques that allow the economic, financial, social and sustainable development of economic activities, especially in the Triângulo Mineiro and Alto Paranaíba region. The dissertation is composed of two articles, the first of which was to analyze the Brazilian scientific production on the coffee production chain, in the Administration area, from 2007 to 2017, through a systematic review and bibliometrics. Through the analysis of publications it was possible to highlight its characteristics and authorship, as well as a panorama about its sub-themes and their spheres of analysis, over time. The most frequent sub-themes in the publications were: good practice, consumption, management, internationalization and strategy, and the most studied areas of analysis were: market, region, consumer and industry. On the three laws of bibliometrics, it is indicated that in the present study Lotka's Law was not proved, Zipf's Law was confirmed and the Bradford Law was partially verified. It is pointed out that there has been considerable interest in the subject, with the increase of studies over the years, with a certain constancy of sub-themes and research analysis spheres, which consolidate over time, knowledge about the coffee production chain in Brazil. On the second article, the aim of the research was to analyze the creation of the Denomination of Origin Cerrado Mineiro Region, its strategic role for the producers and the necessary capacities for its creation and implementation. The technical research procedure was the case study, the Denomination of Origin Cerrado Mineiro Region being the case itself, with the organizations and the rural producers that make up the Denomination. We used documentary analysis, interview with a representative of the Cerrado Coffee Growers Federation, holder of the Cerrado Mineiro Region brand, and also a questionnaire with a representative of a rural producer and a rural producer. The results showed that the Denomination of Origin Cerrado Mineiro Region, made up of the Federation of Coffee Growers of the Cerrado, cooperatives, associations, accredited warehouses and exporters, seeks together with its rural producers to produce coffee with ethics, traceability and high quality. objective is to integrate and develop the region, connecting it to producers and roasters. It is observed as an important factor the creation of the Seal of Origin, which helps in the process of differentiation of the coffees produced in the region, before the market. It is evident that the producers are responding to the market, as the demands of the consumers occur, the producers have tried to meet the demands and that, still, the adaptive and absorptive capacities have been developed in this effort of response, since the innovative capacity was little evidenced. The Technological Production resulting from the present research was the elaboration of a map-scheme to follow the absorption and the adaptation of practices of the coffee farmers participating in the Denomination of Origin Cerrado Mineiro Region.